The Use of Flipped Classroom Method in Fostering Students' Speaking Ability at the University of Iqra Buru - Rahman, Abd; Hajar, Ibnu (Universitas Negeri Makassar, 2021)
External and internal factors have been affecting the university students to master speaking skills continuously; as a result, most of them face obstacles in communicating and expressing their ideas through spoken English. This research examines whether the flipped classroom method's use improves students' speaking ability and enhances students' engagement at the University of Iqra Buru. A true experimental pretest-posttest control group design was used in this study. A total of 82 students from two different faculties took as the samples based on the purposive sampling technique, then they divided into two groups, each consisting of 41 people based on a simple random sampling technique. The research instrument was a rubric of a speaking test and a questionnaire. The data were analyzed using inferential statistics through the paired sample and independent-sample t-test. The questionnaire's result was analyzed using a Likert Scale to determine the frequency of student engagement.